WearTrack â€“ Tracking Valuables using Near Field Communication Stickers - Muneeswari, G; Frank Vijay, J (International Journal of Engineering and Technology, 2018)
In modern era, people will not be satisfied with technology until it not only reminds us of our day to day work but also does it for us without draining much of our energy. Any person will acknowledge the fact that we need smarter technology that reminds us what things are to be taken wherever we go or whenever we leave a place. It makes life so much easier if we are told to do things rather than thinking up things to be done on our own.People irrespective of their age, have always been in situations where they have lost their valuable things or have the fear of losing them.So in this paper an attempt is made how a user gets alarmed whenever they leave a place forgetting to take their valuables. The user has a sensorand othersensorsare connected to things which they want to forget to take as they leave a place. All the sensing devices consist of Bluetooth to recognize the user's sensor or to be recognized by it. An alarm is connected in the circuit which switches on whenever they leave the place without the required things. The evaluation results show that the sensors will give 98%accuracy towards the complete Bluetooth connection.Â Â